2018
DOI: 10.1002/jcp.27801
|View full text |Cite
|
Sign up to set email alerts
|

Association between miRNAs expression and signaling pathways of oxidative stress in diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is a major cause of vision reduction in diabetic patients. Hyperglycemia is a known instigator for the development of DR, even though the role of oxidative stress pathways in the pathogenesis of DR is established. The studies indicate that microRNAs (miRNAs) are significant to the etiology of DR; changes in miRNAs expression levels may be associated with onset and progression of DR. In addition, miRNAs have emerged as a useful disease marker due to their availability and stability in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 141 publications
(170 reference statements)
0
11
0
Order By: Relevance
“…miR-142-5p overexpression or IGF1 knockdown could alleviate the pathological impairments of retinal tissue in DR-treated rats. miRNAs exert multiple types of functions including regulation of inflammatory, oxidative stress, angiogenesis, and coagulation in the progression and development of DR. [21][22][23] For instance, the ectopic expressions of miR-21-5p, miR-365, miR-495, or miR-211 promoted cell proliferation and angiogenesis in DR by modulation of maspin/ AKT/ERK, Timp3, Notch/PTEN/Akt, or Sirtuin 1, respectively, [24][25][26][27] while miR-384-3p, miR-145, miR-133b, or miR-181a suppressed retinal neovascularization, oxidative stress, inflammation, and cell proliferation via restraining hexokinase 2, TLR4/NF-κB, ras homolog family member A, or VEGF expressions, respectively. [28][29][30] Although miR-142 has been considered as one of leading functional miRNAs in various cellular events, studies reported that miR-142-5p was implicated in occurrence and progression of DM and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…miR-142-5p overexpression or IGF1 knockdown could alleviate the pathological impairments of retinal tissue in DR-treated rats. miRNAs exert multiple types of functions including regulation of inflammatory, oxidative stress, angiogenesis, and coagulation in the progression and development of DR. [21][22][23] For instance, the ectopic expressions of miR-21-5p, miR-365, miR-495, or miR-211 promoted cell proliferation and angiogenesis in DR by modulation of maspin/ AKT/ERK, Timp3, Notch/PTEN/Akt, or Sirtuin 1, respectively, [24][25][26][27] while miR-384-3p, miR-145, miR-133b, or miR-181a suppressed retinal neovascularization, oxidative stress, inflammation, and cell proliferation via restraining hexokinase 2, TLR4/NF-κB, ras homolog family member A, or VEGF expressions, respectively. [28][29][30] Although miR-142 has been considered as one of leading functional miRNAs in various cellular events, studies reported that miR-142-5p was implicated in occurrence and progression of DM and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been discovered that oxidative stress can upregulate miR-100 in retinal ganglion cells (RGCs), and hydrogen peroxide can induce apoptosis by increasing miR-100 expression. Conversely, diminished miR-100 expression is associated with activation of the AKT pathway, extracellular-signal-regulated kinase (ERK) pathway, and tropomyosin receptor kinase B (TrkB) pathway [42]. And a study in 2014 [43] has found IGF1R (IGF-1 receptor) was directly regulated by miR-100 in RGC-5 cells, and siRNA-mediated IGF1R knockdown activated AKT protein through phosphorylation; downregulated miR-100, thus exerted a protective effect on RGC-5 apoptosis.…”
Section: Mir-100mentioning
confidence: 99%
“…There is an established association between miR-195 and oxidative stress/diabetes-induced retinal endothelial cell injury because of miR-195 acting as a regulator for mitofusin-2 (MFN2), which is known to be involved in oxidative stress and diabetes associated complications [42]. Based on the luciferase report assay, miR-195 binds to the 3'-UTR of MFN2 mRNA and its overexpression can result in the downexpression of MFN2 protein leading to tube formation and an increase in blood-retinal barrier permeability [44], thus leads to DR.…”
Section: Mir-195mentioning
confidence: 99%
“…So far, the most widely studied class of ncRNAs are miRNAs, which are small ncRNAs of ~22 nt that regulate expression of more than 60% of protein‐coding genes, consequently controlling various biological and pathological processes, such as cellular growth, apoptosis, differentiation, metabolism and immune response (Esteller 2011; Assmann et al 2017b; Martinez & Peplow 2019; Satari et al 2019). Growing evidence suggests the involvement of several miRNAs in DR pathogenesis (Joglekar et al 2016; Gong & Su 2017; Kumari et al 2019; Martinez & Peplow 2019; Satari et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the most widely studied class of ncRNAs are miRNAs, which are small ncRNAs of ~22 nt that regulate expression of more than 60% of protein‐coding genes, consequently controlling various biological and pathological processes, such as cellular growth, apoptosis, differentiation, metabolism and immune response (Esteller 2011; Assmann et al 2017b; Martinez & Peplow 2019; Satari et al 2019). Growing evidence suggests the involvement of several miRNAs in DR pathogenesis (Joglekar et al 2016; Gong & Su 2017; Kumari et al 2019; Martinez & Peplow 2019; Satari et al 2019). MiRNA‐126 expression seems to be downregulated in serum of diabetic patients with DR (Rezk et al 2016; Barutta et al 2017; Qin et al 2017; Martinez & Peplow 2019), endothelial cells (ECs) and retinal pericytes of a murine DR model (Fang et al 2017), and in retina of streptozotocin (STZ)‐induced diabetic rats (Ye et al 2014).…”
Section: Introductionmentioning
confidence: 99%